2013
DOI: 10.5114/ninp.2013.39067
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy prior to and in acute ischaemic stroke. The use of pharmacotherapy and drugs-associated outcomes in real-world practice – findings from the Polish Hospital Stroke Registry

Abstract: The prevention of ischaemic stroke needs to be monitored and improved. Evidence-based treatment of acute ischaemic stroke requires further promotion. The benefits of acute ischaemic stroke treatment with statins require to be confirmed in randomized controlled settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…During 1990s the incidence of anticoagulant-associated ICH quintupled in United States and the majority of this change was attributed to increased warfarin use [8]. In our study, 21% of AF patients prior to haemorrhagic stroke were reported oral anticoagulants users (twice more often than AF patients hospitalized with ischaemic stroke) [6]. The corresponding values in other studies were similar and ranged from 18.3 to 23.4% [9,10].…”
Section: Or -Odds Ratio CI -Confidence Intervalsupporting
confidence: 71%
See 3 more Smart Citations
“…During 1990s the incidence of anticoagulant-associated ICH quintupled in United States and the majority of this change was attributed to increased warfarin use [8]. In our study, 21% of AF patients prior to haemorrhagic stroke were reported oral anticoagulants users (twice more often than AF patients hospitalized with ischaemic stroke) [6]. The corresponding values in other studies were similar and ranged from 18.3 to 23.4% [9,10].…”
Section: Or -Odds Ratio CI -Confidence Intervalsupporting
confidence: 71%
“…Alike for ischaemic stroke, drug utilisation before cerebrovascular accident and in acute haemorrhagic stroke is important in monitoring of the current medical practice. It can also point out pharmacotherapy potential benefit or harm in real-world settings as reported for ischaemic stroke patients [6]. Data from the Polish Hospital Stroke Registry provide a unique opportunity both to evaluate the current practice and to provide evidence on possible drug related benefit in haemorrhagic stroke based on everyday clinical practice data.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Study reported oral anticoagulants or statins used in hospital were associated with better stroke outcome. 23 Similarly, a study on potential effects of statins initiated before or within four weeks of stroke demonstrated that post stroke statins were associated with a significant probability of a favorable outcome at 90 days. 24 However, the Chinese Acute Stroke Trial showed that the rates of long-term complete recovery or death and disability were not significantly improved in patients treated with aspirin.…”
Section: Discussionmentioning
confidence: 99%